Specific and Non-specific Factors of Animal-Assisted Interventions Considered in Research: A Systematic Review - Wagner, Cora; Grob, Carmina; Hediger, Karin (Frontiers in Psychology, 2022)
Research on animal-assisted interventions (AAIs) has increased massively in the last few years. But it is still not clear how AAIs work and how important the animal is in such interventions. The aim of this systematic review was to compile the existing state of knowledge about the working mechanisms of AAIs. We searched 12 major electronic databases for previous AAI studies with active control groups. Of 2001 records identified, we included 172 studies in the systematic review. We extracted previously published hypotheses about working mechanisms and factors that have been implicitly considered specific or nonspecific in AAI research by categorizing control conditions using content analysis following Mayring. We found that 84% of the included studies mentioned a hypothesis of working mechanisms, but 16% did not define specific hypotheses. By analyzing their control conditions, we found that in most controlled studies, the animal or the interaction with the animal was implicitly considered as a specific factor for the effects of the AAI. Nonspecific factors such as therapeutic aspects, social interactions, or novelty have also been controlled for. We conclude that AAI research still cannot answer the question of how and why AAIs work. To address this important research gap, we suggest using component studies with innovative control conditions and results from placebo research to address both the specific and nonspecific, contextual factors of AAIs to disentangle its mechanisms.